High and Mighty: Implicit Associations between Space and Social Status - Gagnon, Stephanie; Brunye, Tad; Robin, Cynthia; Mahoney, Caroline; Taylor, Holly A. (Frontiers in Psychology, 2011)
Figurative language, the built environment, and our perceptuo-motor experiences frequently associate social status with physical space. Linguistic references such as high status or climbing the corporate ladder, and built places such as the U.S. Capitol building link social and physical hierarchies. In three experiments we examine the source and extent of these associations by testing whether people implicitly associate abstract social status indicators with concrete representations of spatial topography (level versus mountainous land) and relatively abstract representations of cardinal direction (south and north). Experiment 1 demonstrates speeded performance during an Implicit Association Test (IAT; Greenwald et al., 1998) when average social status is paired with level topography and high status with mountainous topography. Experiments 2 and 3 demonstrate a similar effect but with relatively abstract representations of cardinal direction (south and north), with speeded performance when average and powerful social status are paired with south and north coordinate space, respectively. Abstract concepts of social status are perceived and understood in an inherently spatial world, resulting in powerful associations between abstract social concepts and concrete and abstract notions of physical axes. These associations may prove influential in guiding daily judgments and actions.